Endovascular treatment of posterior fossa arteriovenous malformations. (March 2016) - Robert, T.; Blanc, R.; Ciccio, G.; Gilboa, B.; Fahed, R.; Boissonnet, H.; Redjem, H.; Pistocchi, S.; Bartolini, B.; Piotin, M.
Abstract: Infratentorial arteriovenous malformations (AVM) are rare, representing only 7–15% of cerebral AVM. The concentration of eloquent neurological structures and the high rate of bleeding presentation of AVM in this location complicate the management of such lesions. New therapeutic options, especially in endovascular therapy, have fundamentally modified the treatment strategy and also the outcome of posterior fossa AVM. Between 1999 and 2013, baseline, clinical and angiographic data of cerebral AVM were prospectively collected. We analyzed data from patients treated for a posterior fossa AVM, focusing on risk factors for bleeding, and clinical and angiographic outcomes. Sixty-nine patients (mean age 34 years, male to female ratio 2:1) were consecutively treated for an infratentorial AVM. Fifty-seven presented with hemorrhage, six with focal neurologic deficits, and the remaining six patients were diagnosed incidentally. The Spetzler–Martin grade was <3 in 39 (56.5%) patients. Associated aneurysms were noted in 43.5% of patients. All patients were treated using endovascular procedures, associated with microsurgical resection in nine patients and with stereotactic radiosurgery in six. Mean follow-up was 28.5 months, with angiographic exclusion of the AVM in 72.5% of patients; 21.7% of patients presented a modified Rankin Score ⩾3 at follow-up. Endovascular embolization seems to be a secure approach for posterior fossa AVM although a large number of sessions are necessary to achieve complete obliteration. Multi-disciplinary discussion and management is crucial to obtain the best cure rate without increasing procedural risks.